2008
DOI: 10.3354/ab00090
|View full text |Cite
|
Sign up to set email alerts
|

Influence of food regimes and seasonality on fatty acid composition in the ragworm

Abstract: Nereidid worms are well known to be key prey species for aquatic organisms, including economically important fish (e.g. plaice) and invertebrates (shrimps). Food regimes which include nereidids improve the reproductive fitness of cultured animals, i.e. the 'nereidid effect'. Aquaculture produces huge amounts of sludge, which might be recycled by feeding to the ragworm Nereis diversicolor. Here we analysed the fatty acid profiles in N. diversicolor over 1 yr for a wild population and for ragworms fed with comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
43
4
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 17 publications
7
43
4
3
Order By: Relevance
“…The source of the relatively small amount of DHA produced within the system units that accumulated in the lugworm tissues remains problematical. We do not exclude a bacterial origin for this, perhaps from the small number of Shewenella-or Colwellia-like Gammaproteobacteria present in the system (Ashforth 2008).The fatty acid profiles of other polychaetes whose fatty acids have been characterised is consistent with a widespread occurrence of the proposed pathway in the polychaete clade based on evidence reported for Nereis (Hediste) diversicolor (Bradshaw et al 1990, Luis & Passos 1995, Fidalgo e Costa et al 2000, García-Alonso et al 2008, Nereis virens (Olive et al 2002), a number of deep-sea vent worms (Taghon 1988, Pond et al 2002, Phleger et al 2005) and cold-water detritivorous species (Copeman & Parrish 2003), all of which show the occurrence and prominence of C20:2n-6 (the elongation product of C18:2n-6 from which C20:3n-6 is derived) and lack or low concentration of fatty acids associated with the conventional n-6 and n-3 pathways. The presence of long-chain unsaturated fatty acids in deep-sea vent worms has been considered problematic because of the general acceptance that these fatty acids are normally derived from the abundant sources present in the photic zone (for discussion see Pond et al 2002, Phleger et al 2005.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…The source of the relatively small amount of DHA produced within the system units that accumulated in the lugworm tissues remains problematical. We do not exclude a bacterial origin for this, perhaps from the small number of Shewenella-or Colwellia-like Gammaproteobacteria present in the system (Ashforth 2008).The fatty acid profiles of other polychaetes whose fatty acids have been characterised is consistent with a widespread occurrence of the proposed pathway in the polychaete clade based on evidence reported for Nereis (Hediste) diversicolor (Bradshaw et al 1990, Luis & Passos 1995, Fidalgo e Costa et al 2000, García-Alonso et al 2008, Nereis virens (Olive et al 2002), a number of deep-sea vent worms (Taghon 1988, Pond et al 2002, Phleger et al 2005) and cold-water detritivorous species (Copeman & Parrish 2003), all of which show the occurrence and prominence of C20:2n-6 (the elongation product of C18:2n-6 from which C20:3n-6 is derived) and lack or low concentration of fatty acids associated with the conventional n-6 and n-3 pathways. The presence of long-chain unsaturated fatty acids in deep-sea vent worms has been considered problematic because of the general acceptance that these fatty acids are normally derived from the abundant sources present in the photic zone (for discussion see Pond et al 2002, Phleger et al 2005.…”
supporting
confidence: 61%
“…This provides clear evidence of a dietary independence for many longer chain PUFA which must therefore have been produced within system units. García-Alonso et al (2008) similarly found that the fatty acid profile of the polychaete Nereis diversicolor did not change seasonally and was not noticeably influenced by the fatty acid content of their diets. This implies the existence of mechanisms by which long-chain fatty acids can accumulate in detritivorous polychaete tisses from non-photosynthetic sources.…”
Section: Net Gain Of Specific Fatty Acidsmentioning
confidence: 70%
See 2 more Smart Citations
“…However, their supplies are still largely dependent on wild populations, so can be affected by overfishing and habitat disturbances (Scaps 2003). Also, their nutritional contents are known to vary according to seasonal and environmental conditions (Garcia-Alonso et al 2008), and their biosecurity status has recently been questioned (Vijayan et al 2005). These factors suggest that alternative feeds or alternative production strategies for suitable polychaete species are needed.…”
Section: à2mentioning
confidence: 99%